Relations between Social Support, PTSD Symptoms, and Substance Use in Veterans - Gros, Daniel F. (Psychol Addict Behav, 2016)
Social support plays a significant role in the development, maintenance, and treatment of posttraumatic stress disorder (PTSD). However, there has been little investigation of social support with PTSD and its frequent comorbid conditions and related symptoms. Substance use disorders (SUD) are one set of conditions that have yet to be investigated in combination with PTSD and social support. As compared to civilians, veterans are at increased risk for developing both PTSD and SUD. In this study, veterans (N=171) with symptoms of PTSD (76% met diagnostic criteria) and SUD (83% met diagnostic criteria for any dependence) were recruited and completed clinician-rated and self-report measures of PTSD, SUD, and social support. Overall, low social support was reported in the sample. When controlled for the other disorder's symptoms, PTSD symptoms demonstrated a significant negative relation and SUD symptoms demonstrated a significant positive relation to social support. The PTSD findings are consistent with previous studies on PTSD and social support without SUD comorbidity. However, the SUD findings are inconsistent with previous studies, which focused primarily on older veterans. Together, these findings highlight the significance of social support in individuals with PTSD and SUD, and promote future research within comorbid presentations.